SISTEM KLAUSA DALAM TEKS PIDATO NADIEM MAKARIM PADA HARI GURU NASIONAL PERIODE 2020-2022 PERSPEKTIF HALLIDAY - Reskiana, Reskiana; Hajrah, Hajrah; Mahmudah, Mahmudah (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
The aim of this research is to identify the clause system used by the Minister of Education Nadiem Makarim in his National Teacher’s Day Speech for the 2020-2022 period using Halliday’s perspective. This research is descriptive qualitative research obtained through reading techniques and note-taking techniques. The results of this research show that there are two clause systems used by Nadiem Makarim, namely indicative clauses and imperative clauses. In the 2020-2022 National Teachers Day speech, it was found that declarative indicative clauses were more dominant than imperative clauses. This shows that in his speech Nadiem Makarim conveyed more information or statement than giving offers or orders to the listeners.